Alternative Therapies to Fat Grafting in the Craniofacial Region. Issue 3 (May 2019) - Yoo, Jason J.; Casey, Liann C.; Herweck, Alexandra M.; Thaller, Seth R.
Abstract : Abstract: Autologous fat grafting is a technique with various applications in the craniofacial region ranging from the treatment of wounds, scars, keloids, and soft tissue deformities. In this review, alternative therapies to fat grafting are discussed. These are composed of established therapies like silicone gel or sheeting, corticosteroids, cryotherapy, and laser therapy. Novel applications of negative pressure wound therapy, botulinum toxin A injection, and biologic agents are also reviewed.